Variants, structure and value chain management algorithm - A. P. Tyapukhin (Вестник университета)
The research purpose is to clarify and supplement the Value Chain Management theory and methodology by substantiating its main variants, improving the terminological apparatus and improving the relationships between the links of this chain. Classification methods, analysis and synthesis, induction and deduction were chosen as research methods, and binary matrices formed on the basis of classification attributes and their dichotomies were used as the research tool. The article states the following new results: the necessity of studying the term “value life cycle”; proposes directions for improving the “Management by value” concept in relation to chains in statics and dynamics; develops forms classifications for obtaining value by the consumer and supplier and Value Chain Management objects; and also develops the algorithm for creating consumer and supplier values. The obtained results make it possible to reduce the lost profit of the links in value chain due to the functions rational distribution, powers, performers’responsibility and eliminating organisational barriers on the flows trajectories of various value forms and related resources.